A ceramic tile based on recycling of waste resources and a preparation method thereof

By adding modified scale graphite and ceramic fibers to the raw materials of the ceramic tile and using specific chemical treatment and roasting processes to form an intersecting network structure, the problem of reducing the flexural strength of ceramic tile in the prior art is solved, and ceramic tile with high flexural strength, low water absorption and wear resistance is achieved to meet market demand.

CN119774978APending Publication Date: 2025-04-08HEBEI BOER CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411743534.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art uses waste ceramic tile powder and slag to prepare ceramic tile, resulting in a decrease in the flexural strength of the ceramic tile and affects the quality.

Method used

By reasonably matching raw materials such as waste ceramic tile powder, ceramic tile polishing mud, blast furnace slag, blast furnace ash, bauxite clinker, oxide ultrafine powder, etc., and adding modified scale graphite and ceramic fibers to it, a specific chemical treatment and roasting process is used to form an intersection network structure to improve the flexural strength and wear resistance of ceramic tiles.

Benefits of technology

The tiles have achieved flexural strength of more than 51MPa, water absorption rate is less than 0.3%, and the pit volume is less than 50mm3. It has excellent comprehensive performance, extends service life and meets market demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163040220000061
    Figure BDA0005163040220000061
  • Figure BDA0005163040220000071
    Figure BDA0005163040220000071
Patent Text Reader

Abstract

The present application relates to the technical field of recycling of waste resources, and specifically discloses a ceramic tile based on recycling of waste resources and a preparation method thereof. The ceramic tile is mainly made of the following raw materials in parts by weight: 35-45 parts of waste ceramic tile powder, 20-30 parts of ceramic tile polishing mud, 15-25 parts of blast furnace slag, 10-20 parts of blast furnace ash, 14-18 parts of bauxite clinker, 6-10 parts of oxide ultrafine powder, 2-4 parts of modified flake graphite, 1-3 parts of ceramic fiber, 1-3 parts of sintering aid, 4-6 parts of thermosetting liquid phenolic resin, and the modified flake graphite is obtained by treating the flake graphite with γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyloxy titanate. The ceramic tile not only realizes the recycling of waste resources and reduces environmental pollution, but also has the advantages of high flexural strength, low water absorption, and good wear resistance, prolonging the service life and meeting market demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of recycling of waste resources, and more specifically, it relates to a ceramic tile based on recycling of waste resources and a preparation method thereof. Background Art

[0002] Ceramic tile is a common building material. It is widely used in the building decoration industry because of its strong adaptability, high density, good fire resistance, high hardness, strong oxidation resistance, easy cleaning and strong decorativeness. With the rapid development of the construction industry, the demand for ceramic tiles continues to increase, and a large amount of waste ceramic materials are inevitably generated. How to effectively utilize these waste materials and realize the recycling of resources has become one of the important topics of current research. In recent years, some researchers have tried to use waste materials such as waste ceramic tile powder and slag to make ceramic tiles, which can not only reduce environmental pollution, but also improve resource utilization. However, the applicant found in actual production that the use of waste ceramic tile powder and slag as raw materials can reduce the discharge of waste, but significantly affect the flexural strength of ceramic tiles. Therefore, how to improve the flexural strength of ceramic tiles on the basis of realizing resource recycling and utilization, so as to improve the quality of ceramic tiles, is of great significance to meet market demand. Summary of the invention

[0003] On the basis of realizing the recycling of waste resources, in order to improve the flexural strength of ceramic tiles, the present application provides a ceramic tile based on the recycling of waste resources and a preparation method thereof.

[0004] In the first aspect, the present application provides a ceramic tile based on the recycling of waste resources, adopting the following technical scheme: a ceramic tile based on the recycling of waste resources, the ceramic tile is mainly made of the following raw materials in parts by weight: 35-45 parts of waste ceramic tile powder, 20-30 parts of ceramic tile polishing mud, 15-25 parts of blast furnace slag, 10-20 parts of blast furnace ash, 14-18 parts of bauxite clinker, 6-10 parts of oxide ultrafine powder, 2-4 parts of modified flake graphite, 1-3 parts of ceramic fiber, 1-3 parts of sintering aid, and 4-6 parts of thermosetting liquid phenolic resin, wherein the modified flake graphite is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyloxy titanate.

[0005] The ceramic tile based on the recycling of waste resources of the present application, through the mutual cooperation between the raw materials, not only realizes the recycling of waste resources and reduces environmental pollution, but also enables the ceramic tile to maintain good flexural strength, water absorption rate and wear resistance, and the flexural strength is greater than 51MPa, the water absorption rate is less than 0.3%, and the friction pit volume is less than 50mm 3 , with excellent comprehensive performance, meeting market demand.

[0006] In the raw materials of the ceramic tiles of the present application, waste ceramic tile powder, ceramic tile polishing mud, blast furnace slag, blast furnace ash, bauxite clinker, and oxide ultrafine powder are reasonably matched to keep the ceramic tiles in good mechanical properties. On this basis, modified flake graphite and ceramic fiber are added to the raw materials, and the flake graphite is treated with γ-methacryloxypropyl trimethoxysilane, aluminum oleate, and isopropyl trioleyl titanate, and active groups such as siloxy, aluminumoxy, titanoxy, and ester groups are introduced into the flake graphite to increase the dispersibility, uniformity, and interfacial compatibility of the modified flake graphite, and increase the binding force of the raw embryo. And after roasting, ceramic fiber is matched to form a cross-network structure, increase the silicon content, aluminum content, and titanium content, inhibit grain growth, improve the grain structure of ceramic tiles, increase the network structure and cross-linking density, improve integrity, enhance the flexural strength and wear resistance of ceramic tiles, and extend the service life of ceramic tiles.

[0007] Optionally, the modified flake graphite is prepared by the following method: T1. Mix water and flake graphite, add γ-methacryloxypropyltrimethoxysilane, stir for 1-3 hours, filter, and obtain a grafted solid; T2. Mix ethanol and grafted solid, add aluminum oleate, isopropyl trioleyl titanate and initiator, stir for 2-4 hours, filter, wash and dry to obtain modified flake graphite.

[0008] Optionally, the weight ratio of the flake graphite, γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyl titanate is (9-11):(4-6):(2.5-3.5):(0.5-1.5).

[0009] By adopting the above technical scheme, firstly, γ-methacryloxypropyltrimethoxysilane is grafted onto flake graphite using siloxy groups, and carbon-carbon double bonds are introduced. Then, by using polymerization reaction and under the action of an initiator, aluminum oleate and isopropyl trioleyl titanate are grafted, aluminum groups and titanyl groups are introduced, and modified flake graphite is obtained. By adopting the preparation method of the present application, grafting is carried out in steps, which facilitates the preparation of modified flake graphite, ensures the quality and use effect of the modified flake graphite, and improves the flexural strength and wear resistance of tiles.

[0010] In multiple embodiments, in step T1, the stirring time after adding γ-methacryloxypropyltrimethoxysilane is 2 hours. The time can also be set to 1 hour, 1.5 hours, 2.5 hours, or 3 hours as needed, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0011] In multiple embodiments, in step T2, the stirring time for adding the initiator is 3 hours. The time can also be set to 2 hours, 2.5 hours, 3.5 hours, or 4 hours as needed, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0012] Optionally, the weight ratio of the flake graphite and the initiator is (9-11):(0.1-0.3).

[0013] By adopting the above technical solution, the amount of initiator added is optimized, the cost increased due to excessive initiator addition is reduced, and the reaction is affected by too little initiator addition. When the weight ratio of flake graphite and initiator is selected within (9-11): (0.1-0.3), sufficient reaction can be guaranteed, thereby ensuring the stability and use effect of modified flake graphite. In multiple embodiments, the weight ratio of flake graphite and initiator is 10:02, and the weight ratio can also be set to 9:0.1, 9:0.2, 9:0.3, 10:0.1, 10:0.3, 11:0.1, 11:0.2, 11:0.3 as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Optionally, the initiator is one or more of benzoyl peroxide, cumene hydroperoxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.

[0015] By adopting the above technical solution, the initiator is optimized, which facilitates the selection of the initiator. Moreover, benzoyl peroxide, cumene hydroperoxide, di-tert-butyl peroxide, and tert-butyl perbenzoate can all release free radicals and promote polymerization reaction to achieve the grafting of aluminum oleate and isopropyl trioleyl titanate.

[0016] Optionally, the weight ratio of the flake graphite and water is (9-11):(70-130).

[0017] By adopting the above technical solution, the amount of water added is optimized to ensure the uniformity of the dispersion of flake graphite in water and the stability of the grafting of flake graphite and γ-methacryloxypropyltrimethoxysilane. In multiple embodiments, the weight ratio of flake graphite to water is 1:10, and the weight ratio can also be set to 9:70, 9:100, 9:130, 1:7, 1:13, 11:70, 11:100, 11:130 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Optionally, the weight ratio of the flake graphite and ethanol is (9-11):(70-130).

[0019] By adopting the above technical solution, the amount of ethanol added is optimized to ensure the uniformity of the dispersion of the grafted solid in ethanol, and to ensure the stability of the grafted solid and aluminum oleate and isopropyl trioleyl titanate grafting. In multiple embodiments, the weight ratio of flake graphite to ethanol is 1:10, and the weight ratio can also be set to 9:70, 9:100, 9:130, 1:7, 1:13, 11:70, 11:100, 11:130 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Optionally, the average particle size of the flake graphite used in the modified flake graphite is 10-100 μm, and the average diameter of the ceramic fiber is 3-6 μm and the average length is 20-100 μm.

[0021] By adopting the above technical scheme, the particle size of flake graphite, and the diameter and length of ceramic fiber are optimized, which not only facilitates the selection of flake graphite and ceramic fiber, but also ensures the stability of the raw material source, and can also ensure the uniformity of the dispersion of modified flake graphite and ceramic fiber, enhance the interaction between the two, improve the flexural strength, and reduce the volume of friction pits.

[0022] In multiple embodiments, the average particle size of flake graphite is 75 μm. The average particle size can also be set to 10 μm, 30 μm, 50 μm, 80 μm, 100 μm as needed, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0023] In multiple embodiments, the average diameter of the ceramic fiber is 4 μm and the average length is 50 μm. The average diameter can also be set to 3 μm, 3.5 μm, 4.5 μm, 5 μm, 5.5 μm, and 6 μm as needed. The average length can also be set to 20 μm, 40 μm, 80 μm, and 100 μm as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Optionally, the oxide ultrafine powder is one or more of silicon dioxide ultrafine powder, titanium dioxide ultrafine powder, aluminum oxide ultrafine powder, and zirconium oxide ultrafine powder.

[0025] By adopting the above technical solution, the ultrafine oxide powder is optimized, which facilitates the selection of the ultrafine oxide powder.

[0026] Optionally, the oxide ultrafine powder is three kinds of ultrafine silicon dioxide powder, ultrafine titanium dioxide powder and ultrafine aluminum oxide powder, and the weight ratio of ultrafine silicon dioxide powder, ultrafine titanium dioxide powder and ultrafine aluminum oxide powder is (1-3): (1-3): (1-3). In multiple embodiments, the weight ratio of ultrafine silicon dioxide powder, ultrafine titanium dioxide powder and ultrafine aluminum oxide powder is 3:1:2, and the weight ratio can also be set to 1:1:1, 1:1:3, 1:3:1, 1:3:3, 2:1:1, 2:1:3, 2:3:1, 2:3:3, 3:1:1, 3:1:3, 3:3:1 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Optionally, the average particle size of the ultrafine silicon dioxide powder is 1-10 μm, the average particle size of the ultrafine titanium dioxide powder is 5-15 μm, and the average particle size of the ultrafine aluminum oxide powder is 1-10 μm.

[0028] By adopting the above technical scheme, the particle size of ultrafine silicon dioxide powder, ultrafine titanium dioxide powder and ultrafine aluminum oxide powder can be optimized to ensure a stable source of raw materials, and the uniformity of the dispersion of ultrafine oxide powders can be ensured, thereby improving the flexural strength and wear resistance of tiles.

[0029] In multiple embodiments, the average particle size of silica ultrafine powder is 5μm, the average particle size of titanium dioxide ultrafine powder is 10μm, and the average particle size of alumina ultrafine powder is 3μm. The average particle size of silica ultrafine powder can be set to 1μm, 3μm, 8μm, 10μm as needed, the average particle size of titanium dioxide ultrafine powder can be set to 5μm, 8μm, 13μm, 15μm as needed, and the average particle size of alumina ultrafine powder can be set to 1μm, 5μm, 8μm, 10μm as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Optionally, the sintering aid is one or more of boric acid, borax, phosphoric acid, and barium carbonate.

[0031] By adopting the above technical solution, the sintering aid is optimized, which is convenient for the selection of the sintering aid. Moreover, boric acid, borax, phosphoric acid and barium carbonate can effectively reduce the sintering temperature, improve the sintering efficiency, reduce energy consumption, and facilitate the preparation of ceramic tiles.

[0032] In the second aspect, the present application provides a method for preparing ceramic tiles based on recycling of waste resources, which adopts the following technical solution: A method for preparing ceramic tiles based on recycling of waste resources mainly comprises the following steps: S1. Mixing waste ceramic brick powder, ceramic brick polishing mud, blast furnace slag, blast furnace ash, bauxite clinker, ultrafine oxide powder, modified flake graphite, ceramic fiber, and sintering aid to obtain a premix; S2, mixing the premix and the thermosetting liquid phenolic resin to obtain a mixture; S3, placing the mixed material in a mold, and pressing the mold to obtain a green body; S4. Under the protection of inert gas, the green body is fired and cooled to room temperature to obtain ceramic tiles.

[0033] By adopting the above technical solution, the preparation of ceramic tiles is facilitated.

[0034] Optionally, in the machine compression molding process of step S3, the extrusion molding pressure is 30-35 MPa and the time is 5-15 s; in the roasting process of step S4, the roasting temperature is 1200-1230° C. and the time is 40-60 min.

[0035] By adopting the above technical solution, the pressure and time of extrusion molding are optimized, which can effectively improve the density and uniformity of the green embryo and reduce the porosity. The temperature and time of roasting are also optimized, which can fully sinter the raw materials to form a stable crystal structure and ensure the quality of the tiles.

[0036] In multiple embodiments, the extrusion molding pressure is 33 MPa and the time is 10 s. The pressure can also be set to 30 MPa, 31 MPa, 32 MPa, 34 MPa, 35 MPa as needed. The time can also be set to 5 s, 8 s, 13 s, 15 s as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In multiple embodiments, the calcination temperature is 1220°C and the time is 50 min. The temperature can also be set to 1200°C, 1250°C, 1210°C, 1215°C, 1250°C, 1230°C as needed. The time can also be set to 40 min, 45 min, 55 min, 60 min as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In summary, this application has at least the following beneficial effects: 1. The ceramic tile based on the recycling of waste resources in this application has a flexural strength of more than 51MPa, a water absorption rate of less than 0.3%, and a friction pit volume of less than 50mm through the mutual coordination of raw materials. 3 , and the tiles not only realize the recycling of waste resources and reduce environmental pollution, but also have the advantages of high flexural strength, low water absorption and good wear resistance, extending the service life and meeting market demand.

[0039] 2. In the preparation method of modified flake graphite, γ-methacryloxypropyltrimethoxysilane is first grafted on the flake graphite, and then aluminum oleate and isopropyl trioleyl titanate are grafted to obtain modified flake graphite. It is not only convenient for the preparation of flake graphite, but also introduces active groups such as silicon-oxy, aluminum-oxy, titanium-oxy, and ester groups on the flake graphite to improve dispersibility, uniformity, and interface compatibility. After calcination, combined with ceramic fibers, it not only increases the silicon content, aluminum content, and titanium content, but also forms a cross-network structure, inhibits grain growth, improves grain structure, increases density and cross-linking density, improves integrity, enhances the flexural strength and wear resistance of tiles, and makes tiles show better comprehensive performance. DETAILED DESCRIPTION

[0040] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0041] Preparation Example Preparation Example 1 A modified flake graphite is prepared by the following method: T1. Add 10 g of flake graphite to 100 g of water at a rotation speed of 500 r / min, stir for 5 min, add 5 g of γ-methacryloxypropyltrimethoxysilane, stir for 2 h, filter, and obtain a grafted solid.

[0042] Among them, the average particle size of flake graphite is 75μm, and it is selected from Hebei Qingjiang New Materials Technology Co., Ltd.

[0043] T2. Add the grafted solid to 100 g of ethanol at a rotation speed of 500 r / min and stir for 5 min. Add 3 g of aluminum oleate, 1 g of isopropyl trioleyl titanate and 0.2 g of initiator and stir for 3 h. Filter, wash and dry to obtain modified flake graphite.

[0044] Among them, the initiator is benzoyl peroxide; in the washing treatment, it is first washed once with 50g of ethanol, then washed once with 50g of water with a mass concentration of 50%, and then washed once with 50g of water to complete the washing.

[0045] Preparation Example 2 A modified flake graphite, which is different from Preparation Example 1 in that the added amounts of flake graphite, γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyloxy titanate are different, and the added amount of flake graphite is 10g, the added amount of γ-methacryloxypropyltrimethoxysilane is 4g, the added amount of aluminum oleate is 3.5g, and the added amount of isopropyl trioleyloxy titanate is 0.5g.

[0046] Preparation Example 3 A modified flake graphite, which is different from Preparation Example 1 in that the added amounts of flake graphite, γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyloxy titanate are different, and the added amount of flake graphite is 11g, the added amount of γ-methacryloxypropyltrimethoxysilane is 6g, the added amount of aluminum oleate is 2.5g, and the added amount of isopropyl trioleyloxy titanate is 1.5g. Example

[0047] Table 1 Raw material dosage of ceramic tiles (unit: ×10g) Example 1 A ceramic tile based on the recycling of waste resources, the raw materials and raw material ratios are shown in Table 1.

[0048] Among them, the average particle size of the waste ceramic brick powder is 40μm, the silicon dioxide content in the waste ceramic brick powder is 67wt%, and the aluminum oxide content is 20wt%; the silicon dioxide content in the ceramic brick polishing mud is 75wt%, and the aluminum oxide content is 16wt%; the blast furnace slag is S95 grade slag, and the silicon dioxide content in the blast furnace slag is 41wt%, and the aluminum oxide content is 13wt%; the silicon dioxide content in the blast furnace ash is 48wt%, and the aluminum oxide content is 23wt%; The ceramic fiber is aluminum silicate fiber with an average diameter of 4 μm and an average length of 50 μm, and is selected from Hebei Qingjiang New Material Technology Co., Ltd.; the sintering aid is boric acid; the average particle size of the bauxite clinker is 2 mm, and the silicon dioxide content in the bauxite clinker is 9 wt% and the aluminum oxide content is 85 wt%; the thermosetting liquid phenolic resin is thermosetting phenolic resin SP25, and is selected from Wuhan Jiyesheng Chemical Co., Ltd.; the modified flake graphite is prepared by the method of Preparation Example 1.

[0049] The oxide ultrafine powders are of three types: silica ultrafine powder, titanium dioxide ultrafine powder, and alumina ultrafine powder, and the weight ratio of silica ultrafine powder, titanium dioxide ultrafine powder, and alumina ultrafine powder is 3:1:2, and the average particle size of silica ultrafine powder is 5μm, the average particle size of titanium dioxide ultrafine powder is 10μm, and the average particle size of alumina ultrafine powder is 3μm.

[0050] A method for preparing ceramic tiles based on recycling of waste resources mainly comprises the following steps: S1. Add ceramic tile polishing mud, blast furnace slag, and blast furnace ash to the waste ceramic tile powder and stir for 2 minutes. Add bauxite clinker, ultrafine oxide powder, and sintering aid and stir for 2 minutes. Add modified flake graphite and ceramic fiber and stir for 3 minutes to obtain a premix.

[0051] S2. Add thermosetting liquid phenolic resin to the premix, stir for 5 minutes, and obtain a mixture.

[0052] S3, placing the mixed material in a mold, and pressing the mold to obtain a green body.

[0053] In the machine compression molding process, the extrusion molding pressure is 33 MPa and the time is 10 s.

[0054] S4. Under nitrogen protection, the green body is fired and cooled to 23°C to obtain ceramic tiles.

[0055] The calcination temperature was 1220°C and the calcination time was 50 min.

[0056] Example 2 A ceramic tile based on the recycling of waste resources, which is different from Example 1 in that the raw material ratio of the ceramic tile is different, and the raw material ratio of the ceramic tile is shown in Table 1.

[0057] Example 3 A ceramic tile based on the recycling of waste resources, which is different from Example 1 in that the raw material ratio of the ceramic tile is different, and the raw material ratio of the ceramic tile is shown in Table 1.

[0058] Example 4 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that the source of the modified flake graphite in the raw materials of the ceramic tile is different, and the modified flake graphite is prepared by the method of Preparation Example 2.

[0059] Example 5 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that the source of the modified flake graphite in the raw materials of the ceramic tile is different, and the modified flake graphite is prepared by the method of Preparation Example 3.

[0060] Comparative Example Comparative Example 1 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that modified flake graphite and ceramic fiber are not added to the raw materials of the ceramic tile.

[0061] Comparative Example 2 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that in the raw materials of the ceramic tile, modified flake graphite and ceramic fiber are replaced by equal amounts of flake graphite.

[0062] Comparative Example 3 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that an equal amount of ceramic fiber is used to replace modified flake graphite in the raw materials of the ceramic tile.

[0063] Comparative Example 4 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that an equal amount of flake graphite is used to replace modified flake graphite in the raw materials of the ceramic tile.

[0064] Comparative Example 5 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that in the raw materials of the ceramic tile and in the preparation method of modified flake graphite, an equal amount of γ-methacryloxypropyltrimethoxysilane is used to replace aluminum oleate and isopropyl trioleyl titanate.

[0065] Comparative Example 6 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that in the raw materials of the ceramic tile, in the preparation method of modified flake graphite, an equal amount of aluminum oleate is used to replace isopropyl trioleyl titanate.

[0066] Comparative Example 7 A ceramic tile based on the recycling of waste resources, which differs from Example 1 in that in the raw materials of the ceramic tile, in the preparation method of modified flake graphite, an equal amount of isopropyl trioleyloxy titanate is used to replace aluminum oleate.

[0067] Performance Testing The tiles obtained from Examples 1-5 and Comparative Examples 1-7 were respectively taken and the following performance tests were performed on the tiles. The test results are shown in Table 2.

[0068] Among them, flexural strength test: according to GB / T4741-1999 "Test method for flexural strength of ceramic materials", the flexural strength of tiles is tested.

[0069] Water absorption test: According to GB / T3810.3-2016 "Test methods for ceramic tiles Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density", the water absorption of ceramic tiles is tested.

[0070] Wear resistance test: According to GB / T3810.6-2016 "Test methods for ceramic tiles Part 6: Determination of wear depth of unglazed tiles", the wear pit volume of the ceramic tiles is tested.

[0071] Table 2 Test results Test items Flexural strength / (MPa) Water absorption / (%) <![CDATA[Milling pit volume / (mm 3 )]]> Example 1 53.2 0.15 43 Example 2 52.8 0.17 45 Example 3 51.4 0.22 49 Example 4 52.5 0.18 46 Example 5 51.6 0.21 48 Comparative Example 1 34.2 0.93 109 Comparative Example 2 41.4 0.65 85 Comparative Example 3 39.5 0.73 96 Comparative Example 4 44.3 0.54 77 Comparative Example 5 46.8 0.42 68 Comparative Example 6 49.3 0.32 59 Comparative Example 7 48.5 0.35 63 As can be seen from Table 2, the tiles of the present application have a high flexural strength of 51.4-53.2 MPa, showing the characteristics of high flexural strength. In addition, they also have a low water absorption rate and friction pit volume, with a water absorption rate of 0.15-0.22% and a friction pit volume of 43-49 mm. 3 , showing the characteristics of low water absorption and high wear resistance. The ceramic tile of the present application, through the mutual cooperation between the raw materials, not only realizes the recycling of waste resources and reduces environmental pollution, but also makes the ceramic tile have excellent flexural strength, water absorption and wear resistance, meeting market demand.

[0072] Comparative Examples 1-3 are compared. In Comparative Example 1, no flake graphite or ceramic fiber is added to the raw materials of the ceramic tile; in Comparative Example 2, flake graphite is added to the raw materials of the ceramic tile; in Comparative Example 3, ceramic fiber is added to the raw materials of the ceramic tile; in Comparative Example 4, flake graphite and ceramic fiber are added to the raw materials of the ceramic tile. It can be seen from this that by adding flake graphite and ceramic fiber to the raw materials of the ceramic tile at the same time and utilizing the synergistic effect between them, a cross network can be formed, the binding force can be increased, the flexural strength can be improved, and the water absorption rate and the friction pit volume can be reduced. Combined with Comparative Example 5, modified flake graphite and ceramic fiber are added to the raw materials of the ceramic tile in Comparative Example 5, and the modified flake graphite is obtained by treating the flake graphite with γ-methacryloxypropyltrimethoxysilane. It can be seen from this that the flake graphite is modified and the active groups are grafted on the surface of the flake graphite, which can increase the binding force between the raw materials of the embryo, form a carbon network after calcination, increase the crosslinking density, and further improve the flexural strength and wear resistance of the ceramic tile.

[0073] Example 1 is compared with Comparative Examples 5-7. The modified flake graphite of Comparative Example 5 is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane; the modified flake graphite of Comparative Example 6 is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane and aluminum oleate; the modified flake graphite of Comparative Example 7 is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane and isopropyl trioleyloxy titanate; the modified flake graphite of Example 1 is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyloxy titanate. It can be seen from this that on the basis of using γ-methacryloxypropyltrimethoxysilane to treat flake graphite, aluminum oleate and isopropyl trioleyl titanate are further grafted by polymerization reaction, and aluminum radicals and titanyl radicals are introduced on the surface. By utilizing their mutual coordination, the aluminum and titanium contents in the tiles are increased, the interaction between the modified flake graphite and ceramic fibers is enhanced, the flexural strength and wear resistance of the tiles are improved, and the tiles exhibit better overall performance.

[0074] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A ceramic tile based on the recycling of waste resources, characterized by: The ceramic tile is mainly made of the following raw materials in parts by weight: 35-45 parts of waste ceramic tile powder, 20-30 parts of ceramic tile polishing mud, 15-25 parts of blast furnace slag, 10-20 parts of blast furnace ash, 14-18 parts of bauxite clinker, 6-10 parts of ultrafine oxide powder, 2-4 parts of modified flake graphite, 1-3 parts of ceramic fiber, 1-3 parts of sintering aid, and 4-6 parts of thermosetting liquid phenolic resin. The modified flake graphite is obtained by treating flake graphite with γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyl titanate.

2. The ceramic tile based on recycling of waste resources according to claim 1 is characterized by: The modified flake graphite is prepared by the following method: T1. Mix water and flake graphite, add γ-methacryloxypropyltrimethoxysilane, stir for 1-3 hours, filter, and obtain a grafted solid; T2. Mix ethanol and grafted solid, add aluminum oleate, isopropyl trioleyl titanate and initiator, stir for 2-4 hours, filter, wash and dry to obtain modified flake graphite.

3. The ceramic tile based on recycling of waste resources according to claim 2 is characterized by: The weight ratio of the flake graphite, γ-methacryloxypropyltrimethoxysilane, aluminum oleate, and isopropyl trioleyl titanate is (9-11):(4-6):(2.5-3.5):(0.5-1.5).

4. The ceramic tile based on recycling of waste resources according to claim 2 is characterized by: The weight ratio of the flake graphite and the initiator is (9-11):(0.1-0.3).

5. The ceramic tile based on recycling of waste resources according to claim 2 is characterized by: The initiator is one or more of benzoyl peroxide, cumene hydroperoxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.

6. The ceramic tile based on recycling of waste resources according to claim 1 is characterized by: The average particle size of the flake graphite used in the modified flake graphite is 10-100 μm, and the average diameter and average length of the ceramic fiber are 3-6 μm and 20-100 μm, respectively.

7. The ceramic tile based on recycling of waste resources according to claim 1 is characterized by: The ultrafine oxide powder is one or more of ultrafine silicon dioxide powder, ultrafine titanium dioxide powder, ultrafine aluminum oxide powder and ultrafine zirconium oxide powder.

8. The ceramic tile based on recycling of waste resources according to claim 1 is characterized by: The sintering aid is one or more of boric acid, borax, phosphoric acid and barium carbonate.

9. A method for preparing ceramic tiles based on recycling of waste resources as claimed in any one of claims 1 to 8, characterized in that: The main steps are as follows: S1. Mixing waste ceramic brick powder, ceramic brick polishing mud, blast furnace slag, blast furnace ash, bauxite clinker, ultrafine oxide powder, modified flake graphite, ceramic fiber, and sintering aid to obtain a premix; S2, mixing the premix and the thermosetting liquid phenolic resin to obtain a mixture; S3, placing the mixed material in a mold, and pressing the mold to obtain a green body; S4. Under the protection of inert gas, the green body is fired and cooled to room temperature to obtain ceramic tiles.

10. The method for preparing ceramic tiles based on recycling of waste resources according to claim 9, characterized in that: In the mechanical compression molding process of step S3, the extrusion molding pressure is 30-35MPa and the time is 5-15s; In the calcination process of step S4, the calcination temperature is 1200-1230° C. and the calcination time is 40-60 min.